Optimal Design, Electromagnetic–Thermal Analysis and Application of In-Wheel Permanent Magnet BLDC Motor for E-Mobility - Cetinceviz, Yucel (MDPI AG, 2025)
In this paper, a 96 V, 2.5 kW, 36-slot, and 32-pole brushless direct-current (BLDC) motor is designed, analyzed, and tested in the laboratory and on the prototype vehicle to provide the required output performance for an electric vehicle (EV) according to the rated operating conditions. Applications for in-wheel electric drivetrains have the potential to deliver high efficiency and high torque. Consequently, in-wheel motor topology is proposed for small EVs, and the sizing equations, including primary, stator, and rotor dimensions, are developed step by step for the preliminary design. Then, a multi-goal function is introduced to obtain optimum motor design. This motor has an outer-rotor-type construction. In addition, a concentrated winding arrangement is used, which ensures low-end winding and thus low copper loss. Then, multiphysics using the coupled electromagnetic–thermal analysis is carried out. Elective analysis using the finite element method, a motor prototype, and experimental studies verifies the design effectively.
Keywords: Technology; BLDC; QH301-705.5; T; Physics; QC1-999; Engineering (General). Civil engineering (General); Chemistry; multi-objective optimization; multiphysics analysis; prototype; TA1-2040; Biology (General); analytical sizing; QD1-999; thermal analysis